A Few Case Studies of Polymer Conductors for Lithium-based Batteries - Sen, Sudeshna (2018)
The present thesis demonstrates and discusses polymeric ion and mixed ion-electron conductors for rechargeable batteries based on lithium viz. lithium-ion and lithium-sulphur batteries. The proposed polymer ion conductors in the thesis are discussed primarily as potential alternatives to conventional liquid and solid-crystalline electrolytes in lithium-ion batteries. These discussions are part of Chapters 2-4. On the other hand, the polymer based mixed ion-electron conductor is demonstrated as a novel electrode for lithium-Sulphur battery in Chapter 5. Possibility of application of polymer ion conductors is discussed in the context of Li-S battery in Chapter 6. A distinct correlation between the physical properties and electrochemical performance of the proposed conductors is highlighted in detail in this thesis. Systematic investigation of the ion transport mechanism in the polymeric ion conductors has been carried out using various spectroscopic techniques at different time and length scales. Such detailed investigations demonstrate the key structural and physical parameters for design of alternative polymer conductors for rechargeable batteries. Though the thesis discusses the various polymeric conductors in the context of lithium-based batteries, it is strongly felt that the design strategies are equally likely to be beneficial for different battery chemistries as well as for other electrochemical generation and storage devices. A brief discussion of the contents and highlights of the individual chapters are described below: The thesis comprises of six Chapters. Chapter 1 briefly reviews the important developments and materials of lithium-based batteries, with specific focus on Li-ion and Li-S batteries. It starts with discussions on different types of liquid, solid crystalline and solid-like electrolytes. Their materials characteristics, advantages and disadvantages are discussed in the context of secondary batteries such as lithium-ion and lithium-sulphur batteries. As prospective alternative electrolytes polymer based soft matter electrolytes are discussed in detail. Special emphasis is given to the recent developments in polymer electrolytes and their ion conduction mechanism, which are central themes to this thesis. The importance of investigation of charge transport, typically ion, on electrochemical processes is also briefly discussed in Chapter 1. A brief discussion about the characteristics, materials and non-trivialities of the electrochemical storage process in Li-S battery is also reviewed. Chapter 2A demonstrates a binary polymer physical network based gel (PN-x) electrolyte, comprising of an ionic liquid confined inside a binary polymer system for electrochemical devices such as secondary batteries. The synthesis, physical property and electrochemical performances are studied as a function of content of one of the polymers in this Chapter. A physical network of two polymers with different functional groups leads to multiple interesting consequences. The polymer physical network characteristics determine all physical properties including electrochemical property of the ionic liquid integrated PN based GPE. The conductivities of the proposed gel are nearly an order in magnitude higher than the unconfined ionic liquid electrolyte and displays good dimensional stability and electrochemical performance in a separator-free battery configuration. The ac-impedance spectroscopy, steady shear viscosity measurement, dynamic rheology are employed to study physical properties of the proposed gel polymer electrolyte. Chapter 2B discusses the detailed investigations of the ion transport mechanism of the gel polymer electrolyte, as discussed in Chapter 2A. Ion conduction mechanism is investigated in the light of ion diffusion and solvent dynamics of the entrapped ionic liquid inside the polymer. The studies reveal a heavy influence of network characteristics on the ion conduction mechanism. The influence of solvent dynamics on the ion transport is drastically altered by polymer physical network. Consequently, a drastic change in the ion mobility and nature of predominant charge carrier is observed in the polymer physical network based gel electrolyte. A clear transformation from dual ion conductivity to a predominantly anion conductivity is observed on going from single polymer to a dual polymer network. The spectroscopic tools such as pulsed field gradient nuclear magnetic resonance (PFG–NMR), Brillouin light scattering spectroscopy, ac-impedance spectroscopy, FT-Raman and FTIR spectroscopy were used to elucidate the ion transport mechanism in the Chapter. Chapter 3 demonstrates a simple design strategy of gel polymer electrolyte comprising of a lithium salt (lithium bis(trifluoromethanesulfonyl) imide, LiTFSI) solvated by two plastic crystalline solvents, one a solid (succinonitrile, abbreviated as SN) and another a (room temperature) ionic liquid (1-butyl-1-methyl-pyrrolidinium bis(trifluoromethane sulfonyl) imide, (abbreviated as IL) confined inside a linear network of poly(methyl methacrylate) (PMMA). The concentration of the IL component determines the physical properties of the unconfined electrolyte and when confined inside the polymer network in gel polymer electrolyte. Intrinsic dynamics of one plastic crystal influences the conduction mechanism of gel polymer electrolytes. The enhanced disordering in the plastic phase of succinonitrile by IL doping alters both the local ion environment and viscosity. The proposed plastic crystal electrolytes show predominantly anion conduction (tTFSI ≈ 0.5) however, lithium transference number (tLi ≈ 0.2) is nearly an order higher than the ionic liquid electrolyte (IL-LiTFSI) (tLi ≈ 0.02-0.06), discussed in Chapter 2. The gel polymer electrolyte displayed high mechanical compliability, stable Li-electrode | electrolyte interface, low rate of Al corrosion and stable cyclability. The promising electrochemical performance further justifies simple strategy of employing mixed physical state plasticizers to tune the physical properties of polymer electrolytes requisite for application in rechargeable batteries. Chapter 4A proposes a novel liquid dendrimer–based single ion conducting liquid electrolyte as potential alternative to conventional molecular liquid solvent–salt solutions and conventional solid polymer electrolytes for rechargeable batteries, sensors and actuators. The physical properties are investigated as a function of peripheral functionalities in the first generation poly(propyl ether imine) (G1-PETIM)–lithium salt complexes. The change in peripheral group simultaneously affects the effective physical properties viz. viscosity, ionic conductivity, ion diffusion coefficients, transference numbers and also the electrochemical response. The specific change from ester (–COOR) to cyano (–CN) terminated peripheral group resulted in a remarkable switch over from a high cation (tLi+ = 0.9 for –COOR) to a high anion (tPF6- = 0.8 for –CN) transference number. Chapter 4B presents an analysis of the frequency dependent ionic conductivity of single ion dendrimer conductors by using time temperature scaling principles (TTSPs) and dielectric modeling of the electrode polarization. The TTSP provides information on the salt dissociation and number density of mobile charges and hence provides direct insights into the ion conduction mechanism. Summerfield and Baranovskii–Cordes scaling laws, which are well known TTSPs, have been applied to analyze the ion conductivity. The electrode polarization, which quantifies the number density of mobile charges and ionic mobility, is studied using Macdonald-Coelho model of electrode polarization. The combination of these two theoretical investigations of the experimental data emanating from one technique i.e. ac– impedance spectroscopy, predicts independently the contributions of the effect of mobile ion charges and ionic mobility to ion conduction mechanism. In Chapter 5 focus shifts from polymer ion conductors to polymer mixed ion-electron conductor. The polymer mixed ion-electron conductor is demonstrated as a novel electrode material for Li-S battery. A simple strategy to overcome the challenges towards practical realization of a stable high performance Li–S battery is discussed. A soft mixed conducting polymeric network is utilized to configure sulphur nanoparticle. The soft matter network provides efficient and distinct pathways for lithium and electron conduction simultaneously. A lithiated polyethylene glycol (PEG) based surfactant tethered on ultra-small sulphur nanoparticles and wrapped up with polyaniline (PAni) (abbreviated as S-MIEC) is demonstrated here as an exceptional cathode for Li–S batteries. The S-MIEC is characterized by several methods: powder-X-ray diffraction (PXRD), thermo gravimetric analysis (TGA), fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), ac-impedance spectroscopy and dc current-voltage measurements are performed to evaluate conductivity of S-MIEC cathode. Electrochemical studies such as cyclic voltammetry, galvanostatic charge-discharge cycling, galvanostatic intermittent titration (GITT) are performed to demonstrate feasibility of S-MIEC in the Li–S battery performance. Chapter 6 provides a brief summary of the work carried out as part of this thesis and also demonstrates the future perspective of the present work. Potential of the polymer physical network based gel polymer electrolytes, which are discussed in Chapter 2A-B for lithium-ion batteries, are demonstrated in Li-S battery. The proposed polymer physical network confines higher order lithium polysulfides (typically Li2S8) dissolved in tetraethylene glycol dimethyl ether (TEGDME) based electrolyte (TEGDME-1M LiTFSI). The three dimensional polymer network is proposed to be formed by physical blending of the poly(acrylonitrile) (PAN) with the copolymer of AN and poly(ethylene glycol) methyl ether methacrylate (PEGMA), [ P(AN–co–PEGMA)]. We extend here the similar synthetic approaches as described in Chapter 2A. The approach proposed and demonstrated in this concluding Chapter is expected to mitigate some of the major issues of Li-S chemistry. The proposed Li2S8 confined gel electrolyte exhibits moderately high values of ionic conductivity, 2 × 10-3 Ω-1cm-1 and shows a stable capacity of 350 mAhg-1 over 30 days in a separator free Li-S battery.